Innovative systems for earthquake resistant masonry enclosures in RC buildings - Dias, António Baio (2014)
The Commission of the European Communities has recently funded a research project for the benefit of Associations of Small and Medium Enterprises (SME-AGs), aimed at developing innovative systems for masonry enclosures. More in general, the project deals with external partition systems for reinforced concrete framed buildings, such as infill walls and envelopes, and with internal partitions. The project involves sixteen partners from seven European countries, among which there are seven universities and research centres, five industrial associations, and four small and medium enterprises. In the present contribution, an overview of the main objectives and steps of the project is given. A general summary of the various construction systems that are being developed and designed is given. The future developments in terms of experimental programs, numerical analyses, and final expected outcomes of the project are described.